Village Marketing Digitalization Model: Based on Behavior and Community Readiness - Miftah El Fikri; Muhammad Nasir; Nadia Amelia Poluan; Rizal Ahmad; Dewi Nurmasari Pane; Rahmadani Rahmadani (Utan Kayu Publishing, 2024)
Digitalization is a big question about how to accept and adapt to it. People's behavior and culture are also affected by the development of the internet, especially in tourist areas, which has the potential to use it to meet their needs, shop online, sell to visitors and get important information that can increase the scale of their small business. But of course, this does not happen in Pamah Similir Hamlet–Telagah Village where the community still has limited access to digitalization. Telagah Village is ready to face digitalization, but with several improvements in factors that affect the digitalization of village marketing, namely irritation, credibility, interactivity, accessibility, and transformative, this research was carried out on the application of digitalization. The purpose of this study is to analyze how much the influence factor of Village Marketing Digitalization and how the community is ready to deal with it. The results of this study show that all factors influencing Village Marketing Digitalization have a positive and significant effect on the variables of Village Marketing Digitalization. The influencing factors are Irritation, Credibility, Accesibility, Transformative, and Interactivity Variables. From the model test, the largest direct influence is the transformative variable on the credibility variable with a Tstatistic of 22.259 and a P value of 0.000, while the largest indirect influence is the accesibility variable on the credibility variable through the transformative variable with a Tstatistic of 18.755 and a P value of 0.000. The conclusion of this study shows that the Telagah Village community is ready to accept the digitalization of their village marketing, although there are several priority obstacles in terms of signal reception and the amount of signal obtained, road infrastructure and network stability in the village.